Dental extractions as an alternative treatment in cases of skeletal class I in young adults with severe crowding: Literature review (Research, Society and Development, 2023)
Objective: To determine what type of tooth extractions are the most common to use as a treatment alternative for skeletal class I cases in young adults with severe crowding. Materials and Methods: The literature was selected by searching the following electronic databases: PubMed, LILACS, Scopus, Cochrane, Epistemonikos, Pesquisa, Taylor & Francis, Ovid, Dialnet, ProQuest, and Google Academic. The keywords used were: Malocclusion, skeletal class I, dental Extractions, and dental crowding. The search was restricted to English, Spanish, and Portuguese articles published from 2018 to 2023. Results: After applying the inclusion criteria, 24 articles were obtained and reviewed. Determining that the primary crowding solution for the lower front teeth is a tooth extraction or using interproximal enamel reduction methods; crowding results in misaligned teeth and malocclusion. Conclusion: The available literature revealed that the decision about extraction and non-extraction is individual for each case; the extraction of the first four premolars significantly improves dental esthetics and gingival margin, giving the patient a pleasant and harmonious smile and providing stability for years to come.